Recurrent Septic Arthritis Due to Achromobacter xylosoxidans in a Patient With Granulomatosis With Polyangiitis. (28th September 2015) - Patel, Payal K.; von Keudell, Arvind; Moroder, Philipp; Appleton, Paul; Wigmore, Robin; Rodriguez, Edward K.
Abstract: We report a case of recurrent Achromobacter xylosoxidans infections including bacteremia, sepsis, septic joints and endocarditis in a 72 year old female with granulomatosis with polyangiitis. Achromobacter xylosoxidans is a gram negative bacteria increasingly identified in immunocompromised patients. Surgical and medical therapy may need to be combined.